Green Synthesis Carbon Dots Limbah Kulit Alpukat Untuk Optimasi Pertumbuhan Tanaman - Rahmadanti, Zahra (Newton-Maxwell Journal of Physics, 2025)
Green synthesis of carbon dots (C-dots) from fruit peel waste offers an environmentally friendly solution in agriculture. This study aims to synthesize and evaluate the effectiveness of C-dots from avocado and papaya peels in increasing the growth of caisim and chili plants. Characterization using a UV-Vis spectrophotometer confirmed the presence of C-dots with an absorbance peak of 284 nm on papaya skin and 234-400 nm on avocado skin. Growth test results showed that caisim treated with C-dots experienced faster growth than the control, with shoots appearing in two days and growth reaching 2.1 cm in ten days. In contrast, chili pepper plants experienced growth inhibition, which was influenced by environmental factors. C-dots from avocado peels proved to be more effective in increasing the growth of caisim than papaya peels. This finding shows the potential of utilizing organic waste as a base material for green technology to increase agricultural productivity in a sustainable manner.